Calculus - Jeffery, R. L. (Toronto] : University of Toronto Press, 1960)
Since first publication in 1954, this text has been widely used in North American universities in introductory courses in science and engineering. It is a streamlined text, in which essential ideas are not buried in endless detail.
5.12 The solution of the area problem of Â 5.9 5.13 The symbol for the definite integral -- 5.14 The double use of symbols -- 5.15 The existence of the definite integral -- 5.16 The definite integral of continuous functions -- 5.17 Abbreviated methods -- 5.18 Area as a function of the variable x and the double meaning of the symbol dA -- 5.19 The existence of the definite integral of a continuous function -- 5.20 The indefinite integral -- 5.21 The fundamental theorem of the integral calculus -- VI: THE TRANSCENDENTAL FUNCTIONS -- 6.1 Transcendental functions
JSTOR
Keywords: Calculus; Calcul infinitésimal.; calculus; MATHEMATICS -- Calculus; Calculus